2016
DOI: 10.1002/ange.201609517
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the Native 24‐mer Ferritin Nanocage into Its Non‐Native 16‐mer Analogue by Insertion of Extra Amino Acid Residues

Abstract: Protein assemblies with high symmetry are widely distributed in nature.M ost efforts so far have focused on repurposing these protein assemblies,astrategy that is ultimately limited by the structures available.T oo vercome this limitation, methods for fabricating novel self-assembling proteins have received intensive interest. Herein, by reengineering the key subunit interfaces of native 24-mer protein cage with octahedral symmetry through amino acid residues insertion, we fabricated a1 6-mer lenticular nanoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Indeed, the gallic acid‐loaded ferritin sample exhibits a similar color to free gallic acid sample, while apoferritin alone has no color (Figure b). Analytical ultracentrifugation revealed that apo rHuHF sedimented as a single discrete species with s 20,w = 18.9 ± 0.1 S (Figure S6, Supporting Information), agreeing with a reported value . As expected, the gallic acid‐loaded ferritin exhibits nearly the same sedimentation coefficient as apo ferritin alone, indicating that ferritin is still a 24‐mer oligomer after the above encapsulation process.…”
supporting
confidence: 86%
“…Indeed, the gallic acid‐loaded ferritin sample exhibits a similar color to free gallic acid sample, while apoferritin alone has no color (Figure b). Analytical ultracentrifugation revealed that apo rHuHF sedimented as a single discrete species with s 20,w = 18.9 ± 0.1 S (Figure S6, Supporting Information), agreeing with a reported value . As expected, the gallic acid‐loaded ferritin exhibits nearly the same sedimentation coefficient as apo ferritin alone, indicating that ferritin is still a 24‐mer oligomer after the above encapsulation process.…”
supporting
confidence: 86%
“…Details of the experimental methods are given in section S1 of the Supporting Information (SI). 15,17 Experiments were performed with the E. coli TOP10 strain (genotype in SI, section S2) and the B.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure protocol was the same as the one described previously for Pseudomonas idrijaensis. 15 Briefly, a bacterial biomass reaching 1 OD600 unit (corresponding to 0.3 g/L bacteria) was prepared in LB medium at 37°C, then centrifuged and washed in minimally complexing medium (MCM buffer). The composition of the MCM buffer was 20 mM 3-(Nmorpholino)propane sulfonic acid (MOPS buffer), 0.41 mM MgCl2, 6 mM (NH4)2SO4, and 10 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin is composed of 24 subunits that self‐assemble into 12 nm cages. The size of the cages can be increased to 16 nm (48 subunits) or decreased to 10 nm (16 subunits) by genetic manipulation (Zhang et al, ; Zhang et al, ). These different sizes may be favorable depending on the intended application.…”
Section: Effect Of Spatial Control On Targetingmentioning
confidence: 99%